2022
DOI: 10.1186/s12913-022-08714-8
|View full text |Cite|
|
Sign up to set email alerts
|

Medical screening tests and vaccination among hospital-based physicians in Israel

Abstract: Background Very few studies have evaluated physician participation in screening tests and vaccinations. The aim was to evaluate attitudes and actual practice of screening tests and vaccinations among hospital-based physicians and to identify factors that predict actual performance. Methods A cross-sectional study including 220 physicians in various specializations. The study was conducted between January 1, 2017 and December 10, 2017. The statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is consistent with other studies’ findings [ 30 ]. In a study conducted among hospital-based physicians in Israel, less than half of physicians actually underwent the tests themselves, although 94% of them reported that they believe in the importance of screening tests for physicians [ 15 ]. Similar findings were reported in other countries regarding non-adherence to regular screening for colorectal, cervical and breast cancer [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other studies’ findings [ 30 ]. In a study conducted among hospital-based physicians in Israel, less than half of physicians actually underwent the tests themselves, although 94% of them reported that they believe in the importance of screening tests for physicians [ 15 ]. Similar findings were reported in other countries regarding non-adherence to regular screening for colorectal, cervical and breast cancer [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of physical activity and insufficient sleeping were among the suboptimal health behaviors reported by HCWs, including physicians, nurses, physician assistants and interns [ 8 , 14 ]. Additionally, physicians do not always adhere to screening tests recommendations even if they are aware to their importance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Yulia Treister-Goltzman.…”
mentioning
confidence: 99%